Fully biobased sustainable elastomers derived from chitin, lignin, and plant oil via grafting strategy and Schiff-base chemistry. (1st April 2023) - Wang, Zhiqiang; Tang, Pengfei; Chen, Shuaishuai; Xing, Yuxian; Yin, Chuantao; Feng, Jiajun; Jiang, Feng
Abstract: With the dramatically increased environmental problems, the rational design of sustainable polymers from renewable feedstocks opens new avenues to reduce the huge pollution impact. The major challenge for sustainable polymers is the decreased mechanical performance compared to that of petroleum-based materials. In this work, fully biobased sustainable elastomers were developed by integrating renewable chitin, lignin, and plant oil into one macromolecule, in which chitin was chosen as the rigid backbone, while a lignin-derived monomer vanillin acrylate (VA) and a plant oil-based monomer lauryl acrylate (LA) were selected as the hard and soft segments for the grafted side chains. A series of Chitin- graft -poly(vanillin acrylate- co -lauryl acrylate) (Chitin- g -P(VA- co -LA)) copolymers with varied feed ratios and chitin contents were synthesized by using reversible addition-fragmentation chain transfer (RAFT) polymerization as an effective grafting strategy. In addition, a dynamic cross-linked network was incorporated via Schiff-base reaction to improve the macroscopic behavior of such kind of chitin graft elastomers. These sustainable elastomers are mechanically strong and show excellent reprocessablity, as well as outstanding UV-blocking property. This strategy is versatile and can inspire the further development of fully biobased sustainable materials from natural resources. Graphical abstract: Unlabelled Image